"Leading to God's Deepening Life": Considerations of Saint Ignatius of Loyola as Spiritual Guide for Ongoing Transformation in Christ. Issue 1 (May 2022) - Looker, Catherine
This article seeks to explore the spiritual guidance of Saint Ignatius of Loyola as a worthy spiritual guide for our time as we consider some ways that we might seek to more clearly understand and authentically live out the call of Christ in our life journey. In this context of considering the work of Ignatius' Spiritual Exercises as a viable tool for such interior conversion, it is necessary for the work of this article to take a closer look at some highlights of Ignatius' own life journey in order to appropriately consider the significance of key sections of his Spiritual Exercises and the dynamics for Christian formation and transformation inherent in these selected texts. I seek to argue that any assessment of our spiritual maturity in Christ finds clear context in our everyday life experiences as Saint Ignatius so aptly demonstrates